Pengembangan Papan Flanel Tema Pekerjaan Kelas III Sekolah Dasar - Wiwit Fitriana; Diana Endah H (Cakrawala: Jurnal Pendidikan, 2017)
This research and development to knowing develompment and feasibility of media a process learning by themathic approach of curriculum KTSP. The research this research and development model Borg and Gall. The population were students third grade of SDN Langse 02 and SDN 7 Gondoharum. The data were obtained through questionare, interview, and documentation. Wiwit Fitriana has produced flanel board combining on picture stories and two-dimension icons made from flannel that packed in topic of work. The result before doing a tryout were obtained from the expert validator of media reached 98% in high appropriate level and the expert validator of material rearched 100% in high appropriate level as well. After doing a tryout, the result showed that: (1) analisys of questionnaire both of school rearched 96% and 98% in high appropriate level, (2) raising data achievement of KKM from 30-50% to 89%-92%, and (3) data of questionnaire from the practitioner both of schools was 100% and 100% in high appropriate level according to the writer indicator.